Identification of novel plasminogen activator inhibitor-1 inhibitors with improved oral bioavailability: Structure optimization of N-acylanthranilic acid derivatives. Issue 4 (15th February 2018) - Yamaoka, Nagahisa; Murano, Kenji; Kodama, Hidehiko; Maeda, Akihisa; Dan, Takashi; Nakabayashi, Tetsuo; Miyata, Toshio; Meguro, Kanji
Graphical abstract: Abstract: Novel plasminogen activator inhibitor-1 (PAI-1) inhibitors with highly improved oral bioavailability were discovered by structure-activity relationship studies on N -acyl-5-chloroanthranilic acid derivatives. Because lipophilic N -acyl groups seemed to be important for the anthranilic acid derivatives to strongly inhibit PAI-1, synthesis of compounds in which 5-chloroanthranilic acid was bound to a variety of highly lipophilic moieties with appropriate linkers was investigated. As the result it appeared that some of the derivatives possessing aryl- or heteroaryl-substituted phenyl groups in the acyl chain had potent in vitro PAI-1 inhibitory activity. Oral absorbability of typical compounds was also evaluated in rats, and compounds 40, 55, 60 and 76 which have diverse chemical structure with each other were selected for further pharmacological evaluation.